Thermal conductivity and crystallography of polypropylene/ polycarbonate/ polypropylene-graft-maleic anhydride polymer blend - Shayuti, M.S.M. (Trans Tech Publications Ltd, 2020)
The effect of blending polycarbonate (PC) into polypropylene (PP) matrix polymer on thermal conductivity and crystal structure was studied. The blends consisted of 5 to 35 of PC with 5 compatibilizer (polypropylene-graft-maleic anhydride or PP-g-MA), were compounded using twin-screw extruder and shaped into standard tests samples by compression molding. The thermal conductivity values for PP/PC/PP-g-MA blends were ranging from 0.22 â 0.24 W/m.K. When compared to Hanshin â Shtrikman model, the highest difference in the thermal conductivity values was 28.2 shown in 90/5/5 composition. The deviation was due to the exclusion of factors such as PC particulates geometry, size, and dispersion in PP matrix. X-ray Diffraction (XRD) test revealed the blendsâ structures comprised of medium-range order domains, referring to imperfect crystals with nano particles. The locations of peaks in the XRD spectrum also suggest that the pure PPâs monoclinic alpha crystal appeared in all PP/PC/PP-g-MA blends and there was no other crystal obtained in the blends. From the result, the discovered traits of crystal structure displayed influence on the thermal conductivity of the blends. At the same time, reactive compatibilization was suspected to take place at the interface of PP and PC phases when PP-g-MA was introduced. Â© 2020 Trans Tech Publications Ltd, Switzerland.